Knowledge of Obstetric Danger Signs among Adolescent and Adult Mothers in Tanzania: A Secondary Data Analysis. Issue 4 (2nd October 2021) - Winner, Michelle Busangu Fatuma; Do, Mai
Abstract: Despite recent increases in the proportion of pregnant adolescents in Tanzania, little is known about their knowledge of pregnancy-related danger signs, which is critical to alleviate adverse outcomes. We used data from the Service Provision Assessment (SPA) 2014–2015 to assess knowledge of at least one danger sign during pregnancy among adolescent and adult women who had obtained antenatal care. Danger-sign knowledge was 49% lower ( p  < .01) among adolescents than among adult women, after controlling for women's and service-related characteristics. The findings have important implications for interventions and services aimed to improve health outcomes of mothers and babies.